Pemikiran Muhammadiyah Tentang Islam Berkemajuan - Putra, Ronika; Lahmi, Ahmad; Asmaret, Desi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
Perkembangan pemikiran Islam dalam Muhammadiyah, terutama pada konsep